SPEECH ACTS USED BY THE MAIN CHARACTER IN "ENCANTO" DISNEY MOVIE - Priyandini, Tiara Adhiesty; Abdullah, Abdullah; Burhamzah, Muftihaturrahmah (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
This study analyzes the types of illocutionary speech acts used by the main character in the Disney movie "Encanto". This study aims to find the type of illocutionary speech act in the Disney movie "Encanto" that is mostly used by the main character, named "Mirabel". This study uses the theory of JR Searle (1979) to analyze the types of speech acts used by the main character in the Disney movie "Encanto". The research method used in this research is descriptive qualitative. The researcher analyzed the types of illocutionary speech acts used by the main character in the Disney movie "Encanto". The researcher found four types of illocutionary speech acts in the film "Encanto", namely representative, directive, expressive, and commissive. In this study, the researcher describes the types of illocutionary speech acts used by "Mirabel" in the movie "Encanto" with 35 extracts as representatives of several types found for each type of illocutionary act proposed by JR Searle (1979).